The Cdh5-CreERT2 transgene causes conditional Shb gene deletion in hematopoietic cells with consequences for immune cell responses to tumors - He, Qi; Li, Xiujuan; Singh, Kailash; Luo, Zhengkang; Meija-Cordova, Mariela; Jamalpour, Maria; Lindahl, Björn; Kriz, Vitezslav; Vuolteenaho, Reetta; Ulvmar, Maria; Welsh, Michael (Scientific reports, 2019)
The tamoxifen-responsive conditional Cdh5-CreERT2 is commonly used for endothelial cell specific conditional deletion of loxP-flanked gene sequences. To address the role of endothelial cell Shb gene for B16F10 melanoma immune responses, tamoxifen-injected Cdh5-CreERT2/WT and Cdh5-CreERT2/Shbflox/flox mice received subcutaneous tumor cell injections. We observed a decrease of tumor myeloid cell Shb mRNA in the tamoxifen treated Cdh5-CreERT2/Shbflox/flox mice, which was not present when the mice had undergone a preceding bone marrow transplantation using wild type bone marrow. Differences in CD4+/FoxP3+ Tregs were similarly abolished by a preceding bone marrow transplantation. In ROSA26-mTmG mice, Cdh5-CreERT2 caused detectable floxing in certain bone marrow populations and in spleen cells. Floxing in bone marrow could be detected two months after tamoxifen treatment. In the spleen, however, floxing was undetectable two months after tamoxifen treatment, suggesting that Cdh5-CreERT2 is operating in a non-renewable population of hematopoietic cells in this organ. These data suggest that conditional gene deletion in hematopoietic cells is a potential confounder in experiments attempting to assess the role of endothelial specific effects. A cautious approach to achieve an endothelial-specific phenotype would be to adopt a strategy that includes a preceding bone marrow transplantation.
Keywords: melanom experimentální; Hematopoietic Stem Cell Transplantation; Cadherins; hematopoetické kmenové buňky; Melanoma, Experimental; Tamoxifen; transplantace hematopoetických kmenových buněk; Endothelial Cells; Neovascularization, Pathologic; proliferace buněk; Proto-Oncogene Proteins; myši transgenní; tamoxifen; myši inbrední C57BL; Bone Marrow Transplantation; zvířata; Animals; transplantace kostní dřeně; myši; Mice, Transgenic; Cell Proliferation; Hematopoietic Stem Cells; patologická angiogeneze; protoonkogenní proteiny; nádorové buněčné linie; Cell Line, Tumor; Disease Models, Animal; Mice; kadheriny; modely nemocí na zvířatech; Antigens, CD; CD antigeny; delece genu; endoteliální buňky; Gene Deletion; Mice, Inbred C57BL